0236 The First Night Effect In Adolescents With And Without Insomnia. (25th May 2022) - Yuksel, Dilara; Arra, Nicole; Dulai, Teji; Volpe, Laila; Camacho, Leticia; Obilor, Todd; Hsu, Carrie; Kiss, Orsolya; Prouty, Devin; Baker, Fiona; de Zambotti, Massimiliano
Abstract: Introduction: Insomnia in adolescence is a common and debilitating condition, and vulnerability to stress is known to play a major role its development. In this study, we investigated the effects of sleeping under stress in a sample of adolescents with and without clinically significant insomnia symptoms. The first night in the laboratory was used as an established experimental paradigm for eliciting stress through exposure to an unfamiliar environment. Methods: Forty-one postpubertal adolescents (18.4 ± 0.7 years) with (n=14, 9 girls) and without (n=27, 16 girls) DSM-5 insomnia symptoms completed two non-consecutive polysomnographic (PSG) nights in the laboratory. Repeated-measures ANOVAs were used to analyze differences in PSG sleep measures between the first and subsequent night, with group (insomnia vs. control) and sex as between-subject factors. Results: Both groups showed a robust stress effect on the first night, characterized by lower sleep efficiency (↓2.2%) and total sleep time (↓6.4%), and more awakenings (↑12.4%) compared with the subsequent night (p<0.05). Both groups also had less non-rapid-eye-movement (NREM) (↓4.9%) and REM (↓18.8%) sleep on the first night. Girls with insomnia had lower amounts of REM sleep than boys with insomnia on both nights (p<0.05). Both groups perceived higher levels of pre-sleep somatic (↑10.3%) and total (↑7.2%) arousal on the first night compared to the subsequent night (p<0.05). For cognitive arousal, there was a night-group-sex interaction effect: while controls showed no changes between the two nights, boys with insomnia reported significantly lower pre-sleep cognitive arousal levels on the subsequent laboratory night compared to the first night (↓32.9%), whereas cognitive arousal levels remained elevated on the subsequent night in girls with insomnia (p<0.05). Conclusion: Sleeping for the first time in the laboratory leads to greater pre-sleep arousal and disrupts sleep in adolescents with and without insomnia symptoms. Longitudinal studies are needed to examine the female vulnerability in the manifestation of stress-related hyperarousal, particularly in the context of insomnia development during adolescence. Support (If Any): This study was supported by the National Heart, Lung and Blood Institute (NHLBI) grant R01 HL139652 (MdZ). The content is solely the responsibility of the authors and does not necessarily represent the official views the National Institutes of Health.